Clause Combining in Gwama (The University of Nairobi Journal of Language and Linguistics, 2026)
This paper presents a preliminary analysis of clause combining in Gwama, a Koman language spoken in Western Ethiopia. Clauses are combined to form a complex unit. Four types of clause combination structures are identified in the language: complement clauses, relative clauses, adverbial clauses, and converbal clauses. When finite complements function as objects, the verbs of the complements are usually morphologically marked in that they take subject markers and aspect morphemes. In complement constructions, two independent clauses are juxtaposed in Gwama. According to the typology of relative clause formation in African languages, all the relative clause constructions in Gwama use a head-internal non-reduction relativization strategy, where the head noun appears as a full-fledged noun phrase in the relative clause and has no explicit representation in the matrix clause. The relative clauses of Gwama are basically postnominal. Temporal, reason, and concessive clauses have their own markers. The Gwama converb constructions meet two of the three requirements that are attested cross-linguistically: syntactically, converbs are subordinate; on the semantic level, converbs generally modify verbs in a clause; and morphologically, converbs have no markers, so root or stem forms of verbs function as non-finite forms. In such clausal constructions in the language, a series of events are conjoined, with the event expressed by the converb appearing anterior to the event expressed by the finite verb.
Keywords: Koman languages; Gwama; clause combining; relativization; converb